Transfiguración nouménica de vértices del triedro ontológico racionalista en la Dialéctica transcendental (krv) Álgebra categorial y conos universales de factorización = Abweichender Titel: Noumenal Transfiguration of Vertices on the Rationalist Ontological Trihedron in Transcendental Dialectic (krv) : Mapping between Categories and Universal Factoring Cones - Llamas Roig, Vicente (Cauriensia, 2025)
Inquiry into the genesis and regulative vigor of νοούμεννον, an epistemic distortion of Plato's νοητόν, which assimilates the form and subsistent being of Thomism. The noumenon is postulated as the limit of gnoseological homomorphism by prosyllogistic ascent to the asymptotic unconditioned unity within the framework of a categorical theory. The conversio ad phantasma yields to the synthesis speciosa (Summa I, q. 84, a. 7: "The soul understands nothing without a phantasm") and the intelligible species becomes, as formalis ratio intelligendi, a pure conceptual form (analogy of proportion, solution of progress to subsistent being, is displaced by the schematic analogon). The essay also proposes an algebraic reading of the apparatus of functors on indexing cones in which the noumenon is established as a malicious vertex.